2016
DOI: 10.1111/1752-1688.12381
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends in Streamflow and Precipitation in Northwest California and Southwest Oregon, 1953‐2012

Abstract: Using nonparametric Mann‐Kendall tests, we assessed long‐term (1953‐2012) trends in streamflow and precipitation in Northern California and Southern Oregon at 26 sites regulated by dams and 41 “unregulated” sites. Few (9%) sites had significant decreasing trends in annual precipitation, but September precipitation declined at 70% of sites. Site characteristics such as runoff type (groundwater, snow, or rain) and dam regulation influenced streamflow trends. Decreasing streamflow trends outnumbered increasing tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 89 publications
1
22
1
1
Order By: Relevance
“…A finding of no significant trend is a common result among studies that use the Mann-Kendall test to identify trends among several sites [39,40], and is more common among precipitation than discharge [36]. This may be due to a break in classification.…”
Section: Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…A finding of no significant trend is a common result among studies that use the Mann-Kendall test to identify trends among several sites [39,40], and is more common among precipitation than discharge [36]. This may be due to a break in classification.…”
Section: Trendsmentioning
confidence: 99%
“…Research has indicated that climate and associated hydrologic processes (such as streamflow production) have already begun to change in some parts of the world, including significant downward trends in precipitation in parts of India [34] and New Zealand [35], as well as downward trends in dry-season streamflow and upward trends in peak streamflow in parts of the United States [36][37][38][39][40]. If temperate dry-summer climate zones are undergoing changes in climate variables-such as increased or decreased annual precipitation-these changes could already be causing shifts in ecological community composition and structure.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, there is a need to connect the fate of summer stream flow to land use practices (e.g., Price et al, ; Reed et al, ; Strauch et al, ; Sun et al, ; Weitzell et al, ), including water extraction (e.g., Arroita et al, ), as well as anticipated climate change (e.g., Asarian & Walker, ). In the Northern California Coast Ranges specifically, rapid expansion of cannabis cultivation is putting extreme pressure on summer water resources (e.g., Bauer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of factors in a watershed can contribute to low flow conditions in coastal California [43], many of them a result of legacy forest management issues having to do with fine sediment accumulation [44] and forest regeneration [45]. Other important lessons learned in Grape Creek were the importance of a healthy egosystem, where landowners and non-regulatory conservation partners could work together to solve problems without fear of regulatory overreach; and the importance of federal funding for dual purposes of supporting endangered species and enhancing individuals' water supply security.…”
Section: Grape Creekmentioning
confidence: 99%